2014
DOI: 10.1007/s40262-014-0150-5
|View full text |Cite
|
Sign up to set email alerts
|

Why Dried Blood Spots Are an Ideal Tool for CYP1A2 Phenotyping

Abstract: Background and ObjectiveDried blood spot (DBS) sampling has gained wide interest in bioanalysis during the last decade. Also in pharmacokinetic and phenotyping studies, DBS-based sampling has already been successfully applied. However, all available phenotyping studies used small data sets and did not include a systematic evaluation of DBS-specific parameters. The latter is important since several of these factors still challenge the breakthrough of DBS in routine practice. In this study, caffeine and paraxant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Linear calibration curves for caffeine and paraxanthine ranged from 20 to 500 pg/mg, with 20 pg/mg being the lower limit of quantification (LLOQ) for both compounds. Intra-and interbatch precision was below 12% (% relative standard deviation, %RSD) and accuracy below 7% (%bias) for all QCs (20,60,200 and 400 pg/mg).…”
Section: Hair Sample Collection Pretreatment and Analysismentioning
confidence: 89%
See 3 more Smart Citations
“…Linear calibration curves for caffeine and paraxanthine ranged from 20 to 500 pg/mg, with 20 pg/mg being the lower limit of quantification (LLOQ) for both compounds. Intra-and interbatch precision was below 12% (% relative standard deviation, %RSD) and accuracy below 7% (%bias) for all QCs (20,60,200 and 400 pg/mg).…”
Section: Hair Sample Collection Pretreatment and Analysismentioning
confidence: 89%
“…For 4 volunteers, a segmental analysis of 6 consecutive 3-cm hair segments was performed as well. At the day of hair sampling, a standard CYP1A2 phenotyping procedure was conducted in the same study population, as described elsewhere [20]. Briefly, caffeine and paraxanthine concentrations were determined with a validated method in plasma samples from volunteers that had taken a 150 mg caffeine capsule 6 hours (± 5 minutes) before sample collection [20,22].…”
Section: Cyp1a2 Phenotyping Studymentioning
confidence: 99%
See 2 more Smart Citations
“…As a consequence, Bland-Altman and Passing-Bablok plots showed that paraxanthine/caffeine ratios, i.e. the CYP1A2 phenotyping metric, were highly comparable in all matrices [41].…”
Section: Dried Blood Spotsmentioning
confidence: 92%